ASSESSMENT OF THE ADULT'S PERSONAL DEVELOPMENT AS AN INDICATOR OF THE QUALITY OF FURTHER EDUCATION - Natalya A. Biryukova (National Research Mordova State University, 2016)
Introduction: development of international cooperation in different spheres of human activity requires a foreign language proficiency. That is why the issue of improving the process of teaching a foreign language during further education has acquired a special timeliness. In this regard there is a need for monitoring the quality of programmes of further adult education. However, the monitoring process is complicated because of the lack of unified standards and clear criteria for assessment. Materials and Methods: as a basic criterion for evaluating the effeciency of adult education the author explores the level of a learner's personal development. The paper discusses the main difficulties and barriers that make the learning process more difficult. The results of diagnostics of personal development of students of the educational programme "English without barriers" taught at Mari State University are discussed. Results: monitoring results have revealed positive dynamics for each personal criterion (motivational, cognitive, communicative) used to assess the quality of the programme of further adult education: level of language knowledge and skills has increased as well as the level of motivation of achievement; a positive communicative approach has developed; level of learners' sociability has increased. Discussion and Conclusions: the study showed that one of the most important effects of adult education is represented by students' personal growth, also traceable in the development of cognitive, motivational and communicative spheres of personality. The highlighted effects can be used as basic criteria to evaluate the effeciency of educational activities of adults.